Knowledge Mapping of Immunotherapy for Hepatocellular Carcinoma: A Bibliometric Study - Shen, Jianming; Shen, Hui; Ke, Lixin; Chen, Jialin; Dang, Xi; Liu, Baoxian; Hua, Yunpeng (Frontiers in Immunology, 2022)
Background Hepatocellular carcinoma (HCC) is one of the most common malignant tumors, and many patients are diagnosed with advanced disease. The treatment of advanced liver cancer has made significant strides in recent years, owing to the practice of immunotherapy drugs. Numerous studies have been published on immunotherapy for HCC; however, no relevant bibliometric study has been published. This study aims to gain a better understanding of the current situation and to identify potential new research directions by conducting a bibliometric analysis on immunotherapy for HCC. Methods We searched the Web of Science Core Collection (WoSCC) for articles related to immunotherapy for HCC. Three software (VOSviewer, CiteSpace, and python) were primarily used to assess the contribution and co-occurrence relationships of various countries/regions, institutes, journals, and, authors as well as to identify research hotspots and promising future trends in this research field. Results A total of 1,641 English articles published between 2011 and 2020 were collected, with the number of articles increasing nearly every year. The majority of publications originated from China (n = 893, 54.42%), followed by the United States and Japan. The Sun Yat-sen University contributed the most publications (n = 97, 5.91%). Nakatsura Tetsuya (n = 26) and Llovet JM (n = 366) were ranked first in the top ten authors and co-cited authors. Cancer Immunology Immunotherapy was the most productive academic journal on immunotherapy for HCC [n = 46, 2.80%; impact factor (IF) 2020 = 6.9679]. Aggregation and identification of critical nodes in the co-cited network demonstrated a shift in the field of HCC immunotherapy. Initially, the hotspots were predominantly “glypican-3”, “cytokine-induced killer cells”, and “ny-eso-1”, while the emphasis has shifted in recent years to “landscape”, “camrelizumab”, “combination therapy”, and “immune score”. Conclusion Increased attention has been paid to HCC with the advancement of immunotherapy. At the moment, the most active frontiers are focused on better understanding the immunological landscape of liver cancer, screening the population that can benefit from immunotherapy, and the clinical application of immune checkpoint inhibitors, particularly in combination with other therapeutic options (such as local therapy and targeted therapy).